2000
DOI: 10.1007/pl00008652
|View full text |Cite
|
Sign up to set email alerts
|

Structure and regulation of the dnaA promoter region in three Streptomyces species

Abstract: The regulatory region of the Streptomyces dnaA gene comprises a single promoter and two DnaA boxes that are located upstream of the promoter. Comparative analysis of the dnaA promoter region from S. chrysomallus, S. lividans and S. reticuli revealed that the location, spacing and orientation of the DnaA boxes are conserved. In vitro studies demonstrated that efficient binding of the Streptomyces DnaA protein to DNA requires the presence of two DnaA boxes. In vivo analysis of dnaA promoter mutants deleted for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…However, only the dnaA-dnaN region was required to achieve a functional origin when subcloned onto a plasmid, although the rpmH-dnaA DnaA-box clusters did have an effect on origin replication. As before, dnaA transcription was autoregulated by binding of DnaA to DnaA-box clusters in the dnaA promoter (28).…”
Section: Oric Architecturesupporting
confidence: 58%
“…However, only the dnaA-dnaN region was required to achieve a functional origin when subcloned onto a plasmid, although the rpmH-dnaA DnaA-box clusters did have an effect on origin replication. As before, dnaA transcription was autoregulated by binding of DnaA to DnaA-box clusters in the dnaA promoter (28).…”
Section: Oric Architecturesupporting
confidence: 58%
“…Thus, the DnaA boxes might serve as regulatory elements. Indeed, the two boxes in the dnaA promoter are bound by DnaA, and the expression of dnaA is autoregulated (19). In addition, we identified clusters of DnaA boxes containing five or six DnaA boxes within a relatively short distance (213 to 329 bp) (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Interestingly, most of the strong DnaA boxes (42 of 51) lie in noncoding DNA regions upstream of genes. In many cases a single strong DnaA box is present in a putative promoter region, and sometimes a strong box is accompanied by a weak one, as illustrated by the promoter region of dnaA itself (19,36). Thus, the DnaA boxes might serve as regulatory elements.…”
Section: Resultsmentioning
confidence: 99%
“…The initiator protein DnaA of Streptomyces contains two dimerization domains (I and III) that are separated by a long flexible domain II. According to our preliminary results (16,22), interaction of the DnaA protein with two DnaA boxes exhibits cooperativity (e.g. the DnaA protein specifically binds to DNA fragments with two "weak" DnaA boxes, which are not bound as individ- The Streptomyces DnaA Protein Prefers the E. coli DnaA Box over Its Own DnaA Box-Analysis of 57 DnaA boxes from three different Streptomyces oriC regions showed that the preferred sequence is 5Ј-TTGTCCACA-3Ј ("strong" DnaA box).…”
Section: Discussionmentioning
confidence: 99%